Development of Gluten-free Baked Nachos Using Watermelon Rind Powder for Assessment of Physicochemical and Sensory Attributes - Bashir, Mubeen; Shaukat, Amal; Fatima, Tehreem; Fatima, Safa; Hanif, Maha; Shahid, Fatima; Shahid, Komal; Khursheed, Saliha; Javed, Shanza; Rehman, Farwa (Biological and Clinical Sciences Research Journal, 2025)
Watermelon (Citrullus lanatus) is a widely cultivated fruit, primarily consumed for its sweet, nutrient-rich flesh. However, the rind, which constitutes a significant portion of the fruit, is commonly discarded as agricultural waste despite its emerging potential as a value-added food ingredient. Recent research suggests that watermelon rind is rich in bioactive compounds and dietary fiber, making it a promising candidate for functional food development, especially in gluten-free applications. Objective: This study aimed to develop gluten-free baked nachos incorporating watermelon rind powder (WRP) and to evaluate their physicochemical properties, functional characteristics, sensory acceptability, and storage stability. Methods: A laboratory-based experimental study was conducted from January to April 2025. Three treatment formulations were prepared: T₀ (100% corn flour), T₁ (85% corn flour + 15% WRP), and T₂ (80% corn flour + 20% WRP). Watermelon rind powder was prepared using a modified method based on Ogo et al. (2021), while nachos were formulated following a modified protocol from Dubey et al. (2021). Functional properties of the powder blends (swelling capacity, water absorption, and oil absorption) were assessed. Physicochemical analyses of nachos were conducted on days 0, 7, and 14, evaluating moisture content, ash, fat, crude fiber, crude protein, and color using a handheld spectrocolorimeter (Lovibond LC-400). Texture analysis was performed using a TA.XT Plus Texture Analyzer. Microbiological assessment for bacterial and mold counts was conducted to determine shelf stability. Sensory evaluation was carried out by a trained panel (n=10) using a 9-point hedonic scale. Data were analyzed using Statistix 8.1 software, with statistical significance set at p < 0.05. Results: Incorporation of WRP significantly improved the fiber content in T₁ and T₂ compared to the control (T₀). T₂ showed the highest crude fiber and water absorption capacity but slightly reduced sensory acceptability in terms of taste and texture. T₁ achieved the most favorable balance between nutrition and sensory properties. Over the 14-day storage period, all samples remained microbiologically safe, though T₂ exhibited slightly higher moisture retention and texture changes. Color and texture were moderately affected by increasing WRP levels, while functional properties like oil and water absorption improved. Conclusion: Watermelon rind powder is a viable functional ingredient for developing gluten-free snacks such as baked nachos. A 15% substitution level (T₁) demonstrated the most promising results in terms of nutritional enhancement, sensory acceptability, and storage stability. This study supports the valorization of fruit by-products in sustainable food systems and contributes to the development of health-oriented gluten-free products.